2011
DOI: 10.1104/pp.111.187088
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Activities of Plant MicroRNAs: A More Dynamic Perspective

Abstract: Twenty years have elapsed since the discovery of a microRNA (miRNA) gene in Caenorhabditis elegans. Based on growing research progress, we are approaching the nature of this small RNA species, which seemed to be mysterious before. The regulatory activities of miRNAs have been extensively studied through target identification and physiological and phenotypic assays by using bioinformatic, genetic, and biochemical approaches. However, recent evidence points to the fact that the effective levels of miRNAs are det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 159 publications
(208 reference statements)
2
59
0
3
Order By: Relevance
“…The final accumulation of miRNA molecules and consequently the final levels of their mRNA targets result from a combined effect of the regulation of MIR genes transcription as well as the processing of miRNA precursors (Kai and Pasquinelli, 2010;Barciszewska-Pacak et al, 2015). The final levels of mature miRNAs can also be regulated by miRNA degradation or stabilization (Meng et al, 2011). The 10-member Arabidopsis (Arabidopsis thaliana) family of ARGONAUTE proteins is involved in such miRNA stabilization (Kai and Pasquinelli, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The final accumulation of miRNA molecules and consequently the final levels of their mRNA targets result from a combined effect of the regulation of MIR genes transcription as well as the processing of miRNA precursors (Kai and Pasquinelli, 2010;Barciszewska-Pacak et al, 2015). The final levels of mature miRNAs can also be regulated by miRNA degradation or stabilization (Meng et al, 2011). The 10-member Arabidopsis (Arabidopsis thaliana) family of ARGONAUTE proteins is involved in such miRNA stabilization (Kai and Pasquinelli, 2010).…”
mentioning
confidence: 99%
“…This regulation of miRNA expression can be achieved at several levels. It also includes the control of the level of DCL1 and AGO1 mRNA by specific miRNAs (Meng et al, 2011) in a distinctive feedback mechanism. The final accumulation of miRNA molecules and consequently the final levels of their mRNA targets result from a combined effect of the regulation of MIR genes transcription as well as the processing of miRNA precursors (Kai and Pasquinelli, 2010;Barciszewska-Pacak et al, 2015).…”
mentioning
confidence: 99%
“…A number of studies have identifi ed and established the role of other small ncRNAs such as miRNAs and siRNAs in mediating abiotic stress tolerance in plants through sequence-dependent gene silencing at transcriptional and post-transcriptional level (Voinnet 2009 ;Sunkar et al 2012 ;Meng et al 2013 ). In contrast to small ncRNAs, only a few lncRNAs have been identifi ed and functionally characterized further to implicate their involvement in abiotic stress response in plants (Ben Amor et al 2009 ;Contreras-Cubas et al 2012 ).…”
Section: Role Of Lncrnas In Abiotic Stress Tolerancementioning
confidence: 98%
“…However, recent studies revealed some important biological functions of miRNA*s in both plants and animals. 44,58,[111][112][113][114] Here, based on the results obtained from our sRNA-seq-based bioinformatics analysis, we proposed that certain miRNA*s or isomiR*s could act as anti-miRs to inhibit the cognate miRNAs from binding the target transcripts, thus reducing the activities of the miRNAs. It is based on the following evidences: (1) According to the biogenesis model of the plant miRNAs, after DCL1-mediated 2-step processing, miRNA and its miRNA*, forming as a short RNA duplex, were exported to the cytoplasm for loading into the AGO1 complex.…”
Section: Degradome-seqmentioning
confidence: 99%